Paciente de sexo femenino de 66 años de edad con obesidad grado ii, e hipertensión arterial estadio 1. - Cano Avilés, Mariuxi Elizabeth (2018)
Obesity is a pathology accompanied by fundamental complications such as those of respiratory, cardiovascular and metabolic type, as well as diabetes, hypertension, or sleep apnea syndrome. Abdominal obesity affects one in two people in the population aged 10 to 59 years, with the largest cohort aged 40 to 49 representing 74.6% and 50 to 59 years representing 81.4%. The 66-year-old female patient has grade II obesity and arterial hypertension 1. She will have physical activity 5 days a week, this will not help to lose weight, it will only increase the loss of fat mass and thus decrease the risk in the health of the patient. And through the adequate nutritional regimen will improve your clinical condition.